Eight weeks of strength and power training improves club head speed in collegiate golfers - Oranchuk, D. J.; Mannerberg, J. M.; Robinson, T. L.; Nelson, M. C. (The Journal of Strength and Conditioning Research, 2020)
Club head speed (CHS) is a major determinant of drive distance, a key component of golf performance. The purpose of this study was to determine the indirect effects of an 8-week strength and power program on CHS. Twelve (6 men, 6 women) NCAA Division II golfers (20.3 ± 1.5 years) randomly assigned to an intervention or control group underwent either a periodized strength and power program consisting of high-load barbell movements or a bodyweight and rotational movement focused resistance training program. Outcomes were CHS, countermovement jump (CMJ) height, and 1RM back squat (BS), power clean (PC), and deadlift (DL). Dependent t-tests were used to assess differences in outcome variables pre-to-post for each group, independent t-tests were used to assess differences between groups, and Pearson correlations were used to assess associations between CHS and outcome variables. On average, the intervention group experienced improvements in all outcome variables except peak CHS (p = 0.60); the control group displayed no changes in any outcome variable except a decrease in average CHS (p = 0.028). Compared with the control group, the intervention group experienced greater improvements in average CHS, BS, PC, and average and peak CMJ height (p = 0.05). Additionally, CHS had large associations with PC (r = 0.70, p = 0.012), BS (r = 0.64, p = 0.025), DL (r = 0.54, p = 0.068) and CMJ (r = 0.73, p = 0.007). These results suggest that improving muscular strength and power by increasing PC, BS, and CMJ is associated with increased CHS in collegiate golfers. Integrating a high-load, barbell-focused strength and power program may be beneficial for improving CHS and indirectly, golf performance.